2003
DOI: 10.1051/gse:2003017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immune responses of cattle as a means to identify high or low responders and use of a human microarray to differentiate gene expression

Abstract: -An immune response (IR) index to identify cows with high (H) and low (L) antibodymediated immune responses (AMIR) had been previously devised. High AMIR associated with decreased mastitis and improved response to vaccination. Measurement of cell-mediated immune response (CMIR) was not included in the index; therefore various antigen/adjuvant combinations were evaluated as inducers of DTH to be added to the IR-index. The Bacillus Calmette Guérin (BCG)-induced/purified protein derivative (PPD)-elicited tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…If this assumption is correct, then selection for BRD resistance or tolerance may gradually result in an improved generalized disease defense mechanism, possibly a more efficacious immune system. Previous studies have demonstrated that antibody and/or cell-mediated immune responses could be used to improve health and production in cattle (Herná ndez et al, 2003), swine (Mallard et al, 1992(Mallard et al, , 1998, and poultry (Sarke et al, 2000). Further investigations into the genetic mechanisms of disease resistance are certainly warranted.…”
Section: Effect Of Incidencementioning
confidence: 99%
“…If this assumption is correct, then selection for BRD resistance or tolerance may gradually result in an improved generalized disease defense mechanism, possibly a more efficacious immune system. Previous studies have demonstrated that antibody and/or cell-mediated immune responses could be used to improve health and production in cattle (Herná ndez et al, 2003), swine (Mallard et al, 1992(Mallard et al, , 1998, and poultry (Sarke et al, 2000). Further investigations into the genetic mechanisms of disease resistance are certainly warranted.…”
Section: Effect Of Incidencementioning
confidence: 99%
“…If this assumption is correct, then selection for BRD resistance or tolerance based on com-mon treatment or incidence records may result in an improved generalized disease defense mechanism, possibly a more efficacious immune system. Previous studies demonstrated that selection for antibody or cellmediated immune responses, or both, improve health and production in cattle (Herná ndez et al, 2003), swine (Mallard et al, 1992 and1998), and poultry (Pinardvan der Laan et al, 1999). Further investigation of the genetic mechanisms of disease resistance is certainly warranted.…”
Section: Implications To Managementmentioning
confidence: 99%
“…The reasons why healthy, immunocompetent animals may be differently susceptible to immunization are not well understood, but it has been reported that cows could be phenotypically classified as low or high responders, based on the magnitude and kinetics of the Ab response to injection of various antigens [22], [23], [24]. Recognized factors of variation in cows' responsiveness to immunization include, among others, the energy balance derived from feeding regimen, peripartum stress and lactation stage [22], [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recognized factors of variation in cows' responsiveness to immunization include, among others, the energy balance derived from feeding regimen, peripartum stress and lactation stage [22], [23], [24]. In addition to these non-genetic effects, there is growing evidence that the individual's genotype may predetermine immunological responses to infection and vaccination [23], [24], [25]. The Ab response to immunization also appears to be often dependent on the adjuvant adopted.…”
Section: Discussionmentioning
confidence: 99%